1997
DOI: 10.1128/jvi.71.12.9206-9213.1997
|View full text |Cite
|
Sign up to set email alerts
|

Activation of transgene expression by early region 4 is responsible for a high level of persistent transgene expression from adenovirus vectors in vivo

Abstract: The persistence of transgene expression has become a hallmark for adenovirus vector evaluation in vivo.Although not all therapeutic benefit in gene therapy is reliant on long-term transgene expression, it is assumed that the treatment of chronic diseases will require significant persistence of expression. To understand the mechanisms involved in transgene persistence, a number of adenovirus vectors were evaluated in vivo in different strains of mice. Interestingly, the rate of vector genome clearance was not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(25 citation statements)
references
References 58 publications
2
23
0
Order By: Relevance
“…It was thus theorized that removal of all or part of the E4 transcription unit would impair viral replication and gene expression such that an immune response would not be triggered. Rodent models have suggested that the deletion of some or all E4 proteins may affect the length and level of transgene expression; however, this regulation appears to be both tissue and promoter specific (Armentano et al, 1997;Brough et al, 1997;Dedieu et al, 1997;Wang et al, 1997;Lusky et al, 1998;Grave et al, 2000).…”
Section: Second-generation Vectorsmentioning
confidence: 99%
“…It was thus theorized that removal of all or part of the E4 transcription unit would impair viral replication and gene expression such that an immune response would not be triggered. Rodent models have suggested that the deletion of some or all E4 proteins may affect the length and level of transgene expression; however, this regulation appears to be both tissue and promoter specific (Armentano et al, 1997;Brough et al, 1997;Dedieu et al, 1997;Wang et al, 1997;Lusky et al, 1998;Grave et al, 2000).…”
Section: Second-generation Vectorsmentioning
confidence: 99%
“…Additional deletions of viral genes (E2 or E4) were implemented in so-called second generation Ad vectors in an attempt to overcome this problem. The advantages of second generation Ad over FGAd remain controversial as some studies show them to be superior in terms of toxicity and longevity of transgene expression [28][29][30][31][32][33][34][35][36] while others do not [22,[37][38][39][40][41].…”
Section: Early Generation Ad Vectorsmentioning
confidence: 99%
“…First, we had a cell line that complemented only E1 and E2a functions (17) and transient-transfection experiments with 293 cells demonstrated that expression of E4 ORF3 alone could support growth of a virus with E4 deleted, dl1011 (5), although not as well as a virus with the entire E4. Second, previous studies suggested that E4 gene products helped maintain vector transgene expression (2,6,10).…”
Section: Construction Of Av4orf3nbg Plasmid Av4orf3nbg a Newgeneratmentioning
confidence: 99%
“…Quantitative analysis of in vitro ␤-galactosidase expression. A remarkable feature that emerged from infection with the adenoviral vectors with E1 and E4 deleted was that expression of a reporter gene under the control of the cytomegalovirus (CMV) or RSV promoter was influenced by E4 protein expression (2,6,10). Thus, a quantitative ␤-galactosidase assay was used to evaluate transgene expression in a noncomplementing A549 cell background, by comparing the ␤-galactosidase expression of the Av3nBg vector (E4 ϩ ) to that of the Av4orf3nBg vector.…”
Section: Construction Of Av4orf3nbg Plasmid Av4orf3nbg a Newgeneratmentioning
confidence: 99%
See 1 more Smart Citation